2021
DOI: 10.1155/2021/7883723
|View full text |Cite
|
Sign up to set email alerts
|

Association between Uric Acid and In-Hospital Heart Failure in Patients with Acute Myocardial Infarction Undergoing Percutaneous Coronary Intervention

Abstract: Objective. To investigate the association of serum uric acid levels with in-hospital heart failure (HF) in patients with acute myocardial infarction (AMI) who are undergoing percutaneous coronary intervention (PCI). Methods. Two hundred sixteen patients with AMI who were treated with PCI were enrolled in our study. Univariate and multivariate logistic regression analyses were performed to estimate the associations between uric acid levels and the risk of in-hospital HF in AMI patients. Analyses of the areas un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Follow‐up time ranged from 1 to 29 years. These studies were conducted in China, 24 , 25 , 26 Poland, 27 Italy, 28 Japan, 29 USA, 30 , 31 , 32 Turkey, 33 and Korea. 34 Heart failure was diagnosed according to ESC guidelines or based on symptoms, physical signs, and treatment response.…”
Section: Resultsmentioning
confidence: 99%
“…Follow‐up time ranged from 1 to 29 years. These studies were conducted in China, 24 , 25 , 26 Poland, 27 Italy, 28 Japan, 29 USA, 30 , 31 , 32 Turkey, 33 and Korea. 34 Heart failure was diagnosed according to ESC guidelines or based on symptoms, physical signs, and treatment response.…”
Section: Resultsmentioning
confidence: 99%
“…High variability in UA levels may increase the risk of future CV events, highlighting the necessity of maintaining steady SUA levels and avoiding significant fluctuations after PCI in individuals with CAD [ 59 ]. In addition, a major clinical trial reported that elevated UA on admission markedly raised the risk of in-hospital heart failure in individuals with acute MI undergoing PCI [ 60 ]. Taken together, these studies demonstrate the value of SUA in predicting risk after PCI.…”
Section: Introductionmentioning
confidence: 99%